An aluminium nitride based multilayer structure for Love mode surface acoustic wave devices - Aslam, M.Z. (IOP Publishing Ltd, 2020)
Love mode surface acoustic wave (SAW) devices are very useful for sensing in liquid environments. Earlier work on such devices mainly made use of zinc oxide (ZnO) thin films on silicon (Si) or silicon dioxide (SiO2). However, using them for sensing still required protection from contamination from zinc (Zn) in the form of some additional passivation layer. In this work, the objective has been to study an aluminium nitride (AlN)-based multilayer structure that is able to generate SAW Love modes very efficiently. A layer of SiO2 on top of the AlN layer does the trick. A 3D finite element method simulation analysis of the proposed structure (SiO2 /AlN (11Â¯20) /SiO2 /Si (100)) is accordingly performed, and phase velocities, electromechanical coupling coefficients and frequency shift due to mass loading are simulated as a function of the normalized thicknesses of AlN and SiO2 films. It is shown that the optimal normalized thickness identified to be hs2 /Î» = 0.18, hAlN /Î» = 0.45 with AlN c-axis orientation of 30o, and the maximum value of the electromechanical coupling coefficient k2 = 0.58 can be achieved. Even though the value of k2 is comparable to ZnO-based Love mode devices, the phase velocity is 1.5 times higher (5530 m sâ1 compared to 3652 m sâ1). Equally importantly, it is seen that the frequency shift due to mass loading of deionized water (the AlN-based multilayer Love mode sensor) is much higher for that using the ZnO-based multilayer Love mode sensor. Â© 2020 IOP Publishing Ltd Printed in the UK